Linking Life Skills and Norms With Adolescent Substance Use and Delinquency in South Africa. (14th February 2013) - Lai, Mary H.; Graham, John W.; Caldwell, Linda L.; Smith, Edward A.; Bradley, Stephanie A.; Vergnani, Tania; Mathews, Cathy; Wegner, Lisa
<x xml:space="preserve">Abstract</x> We examined factors targeted in two popular prevention approaches with adolescent drug use and delinquency in South Africa. We hypothesized adolescent life skills to be inversely related and perceived norms to be directly related to later drug use and delinquency. Multiple regression and a relative weights approach were conducted for each outcome using a sample of 714 South African adolescents aged 15–19 years (M = 15.8 years, 57% female adolescents). Perceived norms predicted gateway drug use. Conflict resolution skills (inversely) and perceived peer acceptability (directly) predicted harder drug use and delinquency. The "culture of violence" within some South African schools may make conflict resolution skills more salient for preventing harder drug use and delinquency.